Antioxidant extracts of three russula genus species express diverse biological activity - Kostić, Marina (2018)
This study explored the biological properties of three wild growing Russula species (R. integra, R. rosea, R. nigricans) from Serbia. Compositional features and antioxidant, antibacterial, antibiofilm, and cytotoxic activities were analyzed. The studied mushroom species were identified as being rich sources of carbohydrates and of low caloric value. Mannitol was the most abundant free sugar and quinic and malic acids the major organic acids detected. The four tocopherol isoforms were found, and polyunsaturated fatty acids were the predominant fat constituents. Regarding phenolic compounds, P-hydroxybenzoic and cinnamic acids were identified in the prepared methanolic and ethanolic extracts, which displayed antioxidant activity through the inhibition of thiobarbituric acid reactive substances (TBARS) formation and oxidative hemolysis; the highest activity was attributed to the R. nigricans ethanolic extract. This is the first report on the antibacterial and antibiofilm potential of the studied species, with the most promising activity observed towards Streptococcus spp. (0.20–0.78 mg/mL as the minimal inhibitory concentration, MIC). The most promising cytotoxic effect was caused by the R. integra methanolic extract on non-small cell lung cancer cells (NCI-H460). Therefore, due to the observed in vitro bioactive properties, the studied mushrooms arise as a source of functional ingredients with potential to be used in novel nutraceutical and drug formulations, which can be used in the treatment of various diseases and health conditions.